Tropical montane cloud forest, twenty years of ecological research. What have we done and where are we going? - Williams-Linera, Guadalupe (Instituto de Ecología, A.C., 2015)
Tropical montane cloud forest (TMCF) is a current issue. It would appear that TMCF had an extended tradition in ecological research, but it is only during the last 20 years that it has been intensively studied. The last 10 years have seen an impressive development in ecological knowledge and the emergence of several research lines. The objective of this paper is to present a review of the TMCF ecological research published in 1995-2014 to have a retrospective, a current view and a glimpse of future studies in Mexico and, particularly, in the state of Veracruz. Biodiversity and disturbance have been the most addressed issues in TMCF. In the last decade, following disturbance and habitat loss of the TMCF, more applied topics such as ecological restoration and ecosystem services have been consolidated. Forthcoming topics will be relating forest resilience with forest processes, components and climate change effects.